Nutritive value and methane production potential of energy and protein rich feedstuffs fed to livestock in India - SINGH, SULTAN; KUSHWAHA, B P; MISHRA, A K; NAG, S K; ANELE, U Y; SINGH, A; BHATTACHARYA, S; GUPTA, P K; JAYASHANKAR, J (The Indian Journal of Animal Sciences, 2016)
Four protein-rich (groundnut cake-GNC, mustard seed cake-MSC, cotton seed cake-CSC and coconut cake- CNC) and 8 energy-rich (wheat grain-WG, barley grain-BG, oat grain-OG, maize grain-MG, wheat bran A-WBA, wheat bran B-WBB, rice bran-RB, chickpea husk/chuni-GC) feedstuffs were evaluated for their carbohydrate and protein fractions, in vitro dry matter degradability, in vitro methane production and energy loss as methane. Crude protein (CP) and ether extract contents were higher in protein-rich feedstuffs than in energy feedstuffs. High lignin content was noted in CSC, GNC, MSC and RB. Degradable CP fractions of total CP ranged from 0.61 to 0.97 and were higher for protein-rich than energy-rich feedstuffs. On an average, protein-rich feedstuffs had more undegradable CP fraction than the grains or brans. Starch content was highest (P< 0.001) in WBB and least in CSC with values of 369 and 37.3 g/kg DM, respectively. Rapidly degradable carbohydrate fraction (CA) was highest in WG, OG, MG (all energy-rich feedstuffs) and least in RB (6.7 g/kg DM). Similar to the observation made in the protein fractions, protein-rich feedstuffs had more unavailable CHO. Feedstuffs energy loss as methane was highest (P< 0.001) from GC (1.90 Mj/kg DM) and least from MG (1.19 Mj/kg DM). Methane production of the feedstuffs could be predicted from the chemical composition, CP and CHO fractions. On an average, chemical composition and protein fractions were better predictors of CH4 production versus CHO fractions with mean R2 values of 0.94 and 0.80, respectively. Data on relative methane emission from energy and protein rich feeds could be utilized to prepare diets that will lead to less methane production from ruminants.